1992
DOI: 10.1111/j.1432-1033.1992.tb17254.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the antibacterial protein of the giant African snail, Achatina fulica Férussac

Abstract: An expression cDNA library was constructed with poly(A)-rich RNA extracted from the collar of the giant African snail, Achutina fulicu Ferussac. A 1.9-kbp cDNA clone encoding a precursor of antibacterial glycoprotein of the snail, achacin, was isolated from the cDNA expression library. The cDNA sequence contains an open reading frame with 1593-nucleotide residues. The deduced amino acid sequence of this achacin precursor starts with a 29-residue leader peptide followed by a 502-residue mature peptide (56 kDa) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
1
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 46 publications
1
35
1
4
Order By: Relevance
“…Both proteins purportedly form large ion channels in the bacterial membrane in a manner similar to insect defensins. Furthermore, it has been shown that larger antibacterial proteins, such as aplysianin A from the sea hare (41) and achacin from the giant African snail (42), are constitutively secreted rather than secreted under stimulation (i.e. injury).…”
Section: Resultsmentioning
confidence: 99%
“…Both proteins purportedly form large ion channels in the bacterial membrane in a manner similar to insect defensins. Furthermore, it has been shown that larger antibacterial proteins, such as aplysianin A from the sea hare (41) and achacin from the giant African snail (42), are constitutively secreted rather than secreted under stimulation (i.e. injury).…”
Section: Resultsmentioning
confidence: 99%
“…Carp antimicrobial proteins, 27 kD and 31 kD proteins, had potent microbicidal activities (0.018−0.18 mol/L) against different strains of Gram-negative and Gram-positive bacteria (Lemaitre et al, 1996). Furthermore, it has been shown that larger antimicrobial proteins, such as aplysianin A from the sea hare (Takamatsu et al, 1995) and achacin from the giant African snail (Obara et al, 1992), have strong antimicrobial activities. Those proteins purportedly form large ion channels in the bacterial membrane in a manner similar to insect defensins.…”
Section: Discussionmentioning
confidence: 99%
“…No approach to investigate the antibacterial action mechanism was proposed. Nevertheless, in amphibians (Gibson, 1991;Mor et al, 1991;Simmaco et al, 1993;Douglas et al, 1994) and mollusks (Takamatsu et al, 1995 ;Obara et al, 1992), substances are secreted at the body surface that are involved as natural defense factors. These substances have been shown to belong to the defensin family, the members of which are well known for their antibacterial activities as well as their channelforming properties.…”
Section: Discussionmentioning
confidence: 99%
“…Fouz et al (1990) have already pointed out the presence of a glycoprotein in the mucus secretions of the turbot. The molecular cloning of achacin from the giant African snail (Obara et al, 1992) and aplysianin A from the sea hare (Takamatsu et al, 1995) revealed several glycosylation consensus sites in the deduced amino acid sequence. Nevertheless, the presence of a glycosylation site in the sequence is not necessary for inducing ion channels in planar lipid membranes or antibacterial activities since the 31-kDa protein, which is not glycosylated, exhibits this behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation